Effect of Using Artificial Intelligence on Service Frequency and Public Satisfaction - Nurfitarini, Wiwik; Suyoso, Aldo Lovely Arief; Ekowati, Dian (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This study aims to assess how Indonesia's Government Office of Kediri District responds to integrating Artificial Intelligence (AI) in improving service frequency and public satisfaction. An explanatory quantitative approach was adopted to investigate the causal relationship between AI adoption and the two dependent variables—service frequency and public satisfaction—through multiple linear regression analysis, utilizing data from a sample of 15 districts between 2018 and 2023. The study reveals that AI adoption significantly enhances public satisfaction and service frequency. Implementing AI, facilitated through the Digital Service Living Lab (DSLL) platform, increases efficiency, responsiveness, and service quality. The study underscores that AI integration can boost public service effectiveness and efficiency, encouraging local governments to broaden AI usage and invest in staff training and capacity development. This research offers strategic recommendations for governments to expand AI adoption further, strengthen inter-district collaboration, and optimize the use of Electronic Government (E-Government) initiatives to support the goals of smart city and provincial development.